Oxa-Diels–Alder Reaction of Isatins and Acyclic α,β-Unsaturated Methyl Ketones through Cooperative Dienamine and Metal Lewis Acid Catalysis - Liu, Lu; Daka, Philias; Sarkisian, Ryan; Deng, Yongming; Wheeler, Kraig; Wang, Hong (Synthesis, 2014)
Cooperative enamine and metal Lewis acid catalysis was applied to develop an asymmetric oxa-Diels–Alder reaction of isatins and but-3-en-2-ones. Spirooxindole tetrahydropyranones were obtained in good yields (58–86%), moderate stereoselectivities (1.3:1–5.9:1 dr, 50–81% ee), and excellent chemoselectivity.
Keywords: bifunctional catalysis; tandem reactions; Yb(OTf)3; oxa-Diels–Alder reaction; spirooxindoles; tetrahydropyranones